Polymerization of Methylenecyclohexanes Catalyzed by Diimine–Pd Complex. Polymers Having trans- or cis-1,4- and trans-1,3-Cyclohexylene Groups - Takeuchi, Daisuke; Watanabe, Keisuke; Sogo, Kenji; Osakada, Kohtaro (Organometallics, 2015)
Diimine–Pd complex promotes isomerization polymerization of methylenecyclohexane and 4-alkyl-1-methylenecyclohexanes to afford the polymers which contain trans- and cis-1,4-cyclohexylene groups, respectively, along the polymer chain. The polymerization of 3-methyl-1-methylenecyclohexane yields the polymer having trans-1,3-cyclohexylene groups. DSC measurement of a part of the polymers revealed their glass transition at high temperature (T g = 162 and 201 °C).